Design and Analysis of Wideband Single-Layer Reflectarray Antenna for Remote Sensing and Environmental Monitoring - Annal Joy J; Sandeep Kumar Palaniswamy; Sachin Kumar; Malathi Kanagasabai; Ladislau Matekovits (Sensors, 2025)
In this article, a wideband single-layer reflectarray antenna for Ku-band applications is presented. The proposed reflectarray antenna is suitable for applications such as fixed satellite service (FSS), broadcasting satellite service (BSS), earth exploration satellite service (EESS), remote sensing, and environmental monitoring. The developed single element of the proposed reflectarray antenna is made up of a horizontal strip, discrete vertical strips of varying sizes, and circular structures. The reflectarray antenna has 441 elements arranged on a square aperture made of Rogers 5880 substrate, measuring 21 cm × 21 cm. The maximum gain obtained is 26.31 dBi, with a bandwidth of 15.4% of 1 dB gain. The achieved aperture efficiency is 44.4%. The obtained cross-polarizations are less than −21.46 dB for the E-plane and −25.27 dB for the H-plane. The side lobe level is found below −15.06 dB in the E plane and −15.7 dB in the H plane. The side lobe level is minimal at 13.5 GHz, measuring less than −18.2 dB and −18.5 dB in the E and H planes, respectively. The reflectarray antenna designed has a fractional bandwidth of 40%. Hence, the developed antenna is suitable for wide Ku-band applications.